A New Arylalkanone Derived from Myristica ceylanica (Myristicaceae) - Manoranjan, Tharmarajah; Wickramasinghe, Anura; Kumar, Vijaya; Kuganathan, Navaratnarajah (Letters in Organic Chemistry, 2025)
A novel arylalkanone, 1-(2’,6’-dihydroxyphenyl)-4-hydroxy-9-(3”,4”-dihydroxyphenyl)-nonan-1-one (1), along with five known arylalkanones, malbaricone A (2), malbaricone B (3), malbaricone C (4), malbaricone D (5) and 1-(2’, 6’-dihydroxyphenyl) tetradecan-1-one (6), and a dimeric acylphenol, giganteone A (7), which is newly reported for this plant, were isolated and characterized from seed mace of Myristica ceylanica.
Keywords: malabaricone A-C